2014
DOI: 10.1109/tnsre.2014.2323576
|View full text |Cite
|
Sign up to set email alerts
|

Support Vector Regression for Improved Real-Time, Simultaneous Myoelectric Control

Abstract: This study describes the first application of a support vector machine (SVM) based scheme for real-time simultaneous and proportional myoelectric control of multiple degrees of freedom (DOFs). Three DOFs including wrist flexion-extension, abduction-adduction and forearm pronation-supination were investigated with 10 able-bodied subjects and two individuals with transradial limb deficiency (LD). A Fitts' law test involving real-time target acquisition tasks was conducted to compare the usability of the SVM-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
120
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 48 publications
(43 reference statements)
1
120
1
Order By: Relevance
“…Most studies that investigate regression-based control used contraction profiles with combined DoFs in the training protocol [7], [8], [13]- [15]. While combined movements are usually not difficult to execute for able-bodied individuals, they are challenging to acquire by individuals with amputation or congenital limb deficiency as they do not have the intrinsic visual and proprioceptive feedback of the actual limb.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies that investigate regression-based control used contraction profiles with combined DoFs in the training protocol [7], [8], [13]- [15]. While combined movements are usually not difficult to execute for able-bodied individuals, they are challenging to acquire by individuals with amputation or congenital limb deficiency as they do not have the intrinsic visual and proprioceptive feedback of the actual limb.…”
Section: Introductionmentioning
confidence: 99%
“…Third, studies have related forearm surface EMG to multiple DoF finger (Liu et al, 2013; Smith et al, 2009; Smith et al, 2008) and/or hand-wrist (Ameri et al, 2014a; Ameri et al, 2014b; Jiang et al, 2009; Jiang et al, 2012b; Muceli and Farina, 2012; Muceli et al, 2014; Nielsen et al, 2011) forces or kinematics, primarily in able-bodied subjects. Preliminary studies utilized high-density electrode arrays (32–64 + channels) (Liu, Brown, 2013; Muceli and Farina, 2012; Muceli, Jiang, 2014) or indwelling electrodes (Kamavuako et al, 2012; Kamavuako et al, 2014; Smith and Hargrove, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ameri et al . (Ameri, Kamavuako, 2014a) related eight EMG signals to 1- and 2-DoF target displacements. Ten able-bodied subjects achieved average R 2 values from 82–90% and two limb-deficient subjects from 76–84%, depending on the DoF.…”
Section: Introductionmentioning
confidence: 99%
“…Others have successfully demonstrated that users can learn abstract mappings between EMG activity and prosthesis output (Radhakrishnan et al, 2008, Pistohl et al, 2013, Antuvan et al, 2014). Both linear (Hahne et al, 2014, Jiang et al, 2014b, Smith et al, 2015a) and nonlinear (Jiang et al, 2012, Hahne et al, 2014, Kamavuako et al, 2012, Ameri et al, 2014, Ngeo et al, 2014, Muceli and Farina, 2012) methods of mapping EMG activity to prosthesis movement have been evaluated, though a large emphasis of real-time evaluation has focused on linear methods and is commonly motivated by the motor control concept of muscle synergies (Jiang et al, 2009, d’Avella et al, 2006). EMG amplitude estimates (such as root-mean-square or mean absolute value (MAV)) are typically the primary signal feature used as inputs into these systems (Hahne et al, 2014, Jiang et al, 2014b, Smith et al, 2015a), as they positively correlate with contraction intensity (De Luca, 1997).…”
Section: Introductionmentioning
confidence: 99%